Learning style preferences of dental students at a single institution in Riyadh, Saudi Arabia, evaluated using the VARK questionnaire - Aldosari MA; Aljabaa AH; Al-Sehaibany FS; Albarakati SF (Advances in Medical Education and Practice, 2018)
Mohammad A Aldosari, Aljazi H Aljabaa, Fares S Al-Sehaibany, Sahar F Albarakati Department of Pediatric Dentistry and Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi Arabia Background: Students differ in their preferred methods of acquiring, processing, and recalling new information. The aim of this study was to investigate the learning style preferences of undergraduate dental students and examine the influence of gender, Grade Point Average (GPA), and academic year levels on these preferences.Methods: The Arabic version of the visual, aural, read/write, and kinesthetic (VARK) questionnaire was administered to 491 students from the first- to the fifth-year academic classes at the College of Dentistry, King Saud University. Descriptive statistics were used to characterize the learning styles of the students, and Chi-square test and Fisher’s test were used to compare the learning preferences between genders and among academic years. Significance was set at a p-value of <0.05.Results: A total of 368 dental students completed the questionnaire. The multimodal learning style was preferred by 63.04% of the respondents, with the remaining 36% having a unimodal style preference. The aural (A) and the kinesthetic (K) styles were the most preferred unimodal styles. The most common style overall was the quadmodal (VARK) style with 23.64% having this preference. These differences did not reach statistical significance (p>0.05). Females were more likely to prefer a bimodal learning style over a unimodal style (relative risk =2.37). Students with a GPA of “C” were less likely to have a bimodal or a quadmodal style preference compared to students with a GPA of “A” (relative risk =0.34 and 0.36, respectively). Second-year students were less likely to prefer a bimodal over a unimodal style compared to first-year students (relative risk =0.34).Conclusion: The quadmodal VARK style is the preferred learning method chosen by dental students, followed by unimodal aural and kinesthetic styles. Gender was found to influence learning style preferences. Students with a “C” GPA tend to prefer unimodal learning style preferences. The VARK questionnaire is a relatively quick and simple tool to reveal the learning style preferences on an individual or a group level. Dental educators should adjust their delivery methods to approximate the learning preferences of their students. Dental students are encouraged to adapt a multimodal style of learning to improve their academic results. Keywords: VARK, learning styles, dental students, gender, learning preferences